The MapZ-Mediated Methylation of Chemoreceptors Contributes to Pathogenicity of Pseudomonas aeruginosa - Sheng, Shuo; Xin, Lingyi; Yam, Joey Kuok Hoong; Salido, May Margarette; Khong, Nicole Zi Jia; Liu, Qiong; Chea, Rachel Andrea; Li, Hoi Yeung; Yang, Liang; Liang, Zhao-Xun; Xu, Linghui (Frontiers in Microbiology, 2019)
The pathogenic bacterium Pseudomonas aeruginosa is notorious for causing acute and chronic infections in humans. The ability to infect host by P. aeruginosa is dependent on a complex cellular signalling network, which includes a large number of chemosensory signalling pathways that rely on the methyl-accepting chemotaxis proteins (MCPs). We previously found that the second messenger c-di-GMP controls the methylation of an amino acid-detecting MCP via the adaptor protein MapZ. The current study further expands our understanding of the role of c-di-GMP in regulating chemosensory pathways by demonstrating that c-di-GMP governs the methylation of multiple MCPs in P. aeruginosa PAO1. The MCPs under the control of c-di-GMP and MapZ include five MCPs (Aer, CtpH, CptM, PctA and PctB) for detecting oxygen/energy, inorganic phosphate, malate and amino acids, and three MCPs (PA1251, PA1608 and PA2867) for detecting unknown chemoattractant or chemorepellent. Chemotaxis assays showed that overexpression of MapZ hampered the taxis of P. aeruginosa towards chemoattractants and scratch-wounded human cells. Mouse infection experiments demonstrated that a dysfunction in MapZ regulation had a profound negative impact on the dissemination of P. aeruginosa and resulted in attenuated bacterial virulence. The data together suggest that, by controlling the methylation of various MCPs via the adaptor protein MapZ, the cellular level of c-di-GMP is likely to have a profound influence on chemotactic responses and bacterial pathogenesis.